The prevalence and county-level socioeconomic correlates of visual impairment and glasses ownership among rural students in Western China - Guan, Hongyu; Zhang, Yunyun; Wang, Zhijie; Chen, Xiangzhe; Xue, Jing; Ding, Yuxiu (Frontiers in Public Health, 2023)
Objectives Vision health has been a major issue in public health care. The vision problems of children in rural China are of particular concern. Effective policies for children's vision health should consider the heterogeneity of individual health levels and regional differences in healthcare services. This study systematically explored the relationship of student visual impairment and glasses ownership with county-level socioeconomic status (namely, county-level per capita GDP, population density and industrial structure) in rural China. Methods The study sample included 99,670 students in grades 4–9 from 445 schools in 13 counties in Shaanxi Province. From 2014 to 2020, students took school-based vision screening tests and completed sociodemographic questionnaires. Multivariate regressions were used for empirical analysis. Results The prevalence of visual impairment was 30.4% in the total sample, and the rate of visual impairment in girls (34.3%) was higher than that in boys (27.0%). Among visually impaired students, the rate of glasses ownership was only 39.7%, with girls (40.6%) higher than boys (38.8%). The study also found that the visual impairment was significantly correlated with county-level average income, population density and industrial structure, and the glasses ownership was significantly correlated with population density and industrial structure (all p < 0.001). Conclusions The study found that the county-level socioeconomic status was positively and significantly correlated with visual impairment and glasses ownership, respectively. The vision health management services for students should be jointly carried out by the education, medical and public health departments, and additional investment is needed to increase the accessibility and affordability of vision care services, with special focus on poor regions and disadvantaged groups, so as to narrow the gap in vision health services.